CRDSAT Generated by pCARGHO: A New Efficient Lectin‐Based Affinity Tag Method for Safe, Simple, and Low‐Cost Protein Purification. Issue 4 (18th October 2018) - Kriznik, Alexandre; Yéléhé‐Okouma, Mélissa; Lec, Jean‐Christophe; Groshenry, Guillaume; Le Cordier, Hélène; Charron, Christophe; Quinternet, Marc; Mazon, Hortense; Talfournier, François; Boschi‐Muller, Sandrine; Jouzeau, Jean‐Yves; Reboul, Pascal
Abstract : Purification of recombinant proteins remains a bottleneck for downstream processing. The authors engineered a new galectin 3 truncated form (CRDSAT ), functionally and structurally characterized, with preserved solubility and lectinic activity. Taking advantage of these properties, the authors designed an expression vector (pCARGHO), suitable for CRDSAT ‐tagged protein expression in prokaryotes. CRDSAT binds to lactose‐Sepharose with a high specificity and facilitates solubilization of fusion proteins. This tag is structurally stable and can be easily removed from fusion proteins using TEV protease. Furthermore, due to their basic isoelectric point (pI), CRDSAT, and TEV are efficiently eliminated using cationic exchange chromatography. When pI of the protein of interest (POI) and CRDSAT are close, other chromatographic methods are successfully tested. Using CRDSAT tag, the authors purified several proteins from prokaryote and eukaryote origin and demonstrated as examples, the preservation of both Escherichia coli Thioredoxin 1 and human CDC25Bcd activities. Overall, yields of proteins obtained after tag removal are about 5–50 mg per litre of bacterial culture. Our purification method displays various advantages described herein that may greatly interest academic laboratories, biotechnology, and pharmaceutical companies. Abstract : The present work deals with a novel method of affinity purification of proteins of interest (POI) in a single step, based on the lectin activity of the CRDSAT (Carbohydrate Recognition Domain) of Galectin‐3 retaining the ability to bind β‐galactosyl derivatives. CRDSAT is a tag that facilitates solubilization of POI and strongly discriminates POI from other contaminant proteins. Furthermore, CRDSAT ‐POI is easily cleavable by TEV protease.